Multiculturalism and minority rights in the Arab world - Kymlicka, Will; Pfostl, Eva (Oxford University Press, 2014)
Since the Arab Spring, Arab states have become the new front line in the struggle for democratization and for open societies. This book explores how minority claims are framed and debated in the region, and in particular, how political actors draw upon, re-interpret, or resist both the new global discourses of minority rights and more local traditions and practices of co-existence. The chapters include both broad theoretical and historical perspectives as well as more focused case studies (including Western Sahara/Morocco, Algeria, Israel/Palestine; Sudan; United Arab Emirates, and Iraq).